Lessons from Catalonia: advancing sexual and reproductive rights through feminist policymaking and governance - Tània Verge; Montserrat Pineda-Lorenzo (Sexual and Reproductive Health Matters)
As sexual and reproductive rights (SRR) face mounting threats globally, Catalonia’s National Strategy for Sexual and Reproductive Rights showcases how democratic governments can expand SRR through feminist policymaking and governance. Building on the region’s robust public health infrastructure, systemic inequalities have been addressed and care standards improved with innovative policies. Grounded in intersectional feminism and a rights-based approach that prioritises bodily autonomy, universality, accessibility and participation, SRR have been embedded not only into health policies but also into education, workplaces and community frameworks. Key lessons from this experience highlight the importance of feminist expertise and leadership in driving impactful change. Framing SRR as human rights broadens their scope and facilitates collaboration across cabinet portfolios, while institutionalising policies within extant frameworks and services seeks to ensure their sustainability beyond political cycles. Furthermore, transformative SRR policies need not be cost-prohibitive; redesigning public services and training health professionals to deliver empathetic care can also yield significant results. Public engagement and participatory policymaking empower citizens and stakeholders, fostering accountability and a culture of advocacy. Catalonia’s bold and inclusive model, coupled with robust responses to the anti-gender movement, offers a blueprint for governments and advocacy organisations worldwide. [192]